A Survey on Topologies and Controls of Z-Source Matrix Converter - Tri Wahono; Tole Sutikno; Nuryono Satya Widodo; Mochammad Facta (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This paper describes the Z-source matrix converter (ZS-MC) topology which specifically discusses topology and control on the ZS-MC. There are two topologies on the ZS-MC, namely Z-source direct-MC (ZS-DMC) and indirect-MC (ZS-IMC). The difference of each of these topologies is in the number of switching mosfets, where ZS-DMC put on nine switches, while ZS-IMC eighteen switches. ZS-IMC topology overcomes the limitations of traditional MC voltage reinforcement and accommodates the operation of buck and boost converter by reducing the number of switches and providing high efficiency.